Prioritizing Nutrition in India, The Silent Emergency : A Strategy for Commitment Building and Advocacy - CARE India (World Bank, Washington, DC, 2013)
This report provides a background of the situation of nutrition in India and the rationale of the initiative presents an overview of the initiative, details the activities accomplished and the achievements in the state of Jharkhand, and at the national level and finally presents the recommendations and lessons learnt at the state and national level. The primary objectives of the initiative was to demonstrate a set of strategic activities to build commitment for nutrition, raise the level of public discourse about nutrition, build a better understanding of the critical gaps and issues to be addressed and advocate for policy and program directions to address these and enhance the commitment for nutrition. The prioritizing nutrition initiative is situated against the above backdrop. It recognizes that policies which aim to increase nutrition level of Indians are developed at the national level, hence to create conducive environment to achieve the goal of nutrition secure nation it is important to have informed and sensitized political leaders, media and civil society at the national level. As health and nutrition, as well as the other sectoral aspects that impact nutrition are governed by state governments, building political and executive commitment at state levels is imperative. Additionally, the potential power of decentralized governance through Panchayati raj institutions provides an opportunity to bringing nutrition centre-stage to the village agenda.